A state-space behavioral model for CMOS class E power amplifiers. - Reynaert, P. (IEEE Transactions on computer-aided design of integrated circuits and systems)
Class E amplifiers are imposed by time-domain constraints. This makes the design of such amplifiers more difficult than other types of amplifiers. This paper presents a new method to analyze class E power amplifiers using state-space equations. A description by these equations makes it possible to find the correct initial conditions that leads to the steady-state solution of the amplifier. Furthermore, it is possible to derive the power balance of the power amplifier based on its state-space equations. The presented method has shown to be very valuable when designing switched power amplifiers. Furthermore, the method can also be applied for power amplifiers that do not fulfill the class E switching conditions.